Strategi Manajemen Lanskap Berkelanjutan dalam Perkebunan Kelapa Sawit untuk Meningkatkan Kesejahteraan Masyarakat Lokal - Afiantoro, Febri; Suhartati, Tatik; Kifli, Fahmi W. (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
Oil palm plantations play a vital role in Indonesia’s economy; however, the dominance of monoculture practices has led to environmental and social issues such as land degradation and unstable farmer incomes during the replanting period until the first harvest (TM1). To address these challenges, the oil palm–pineapple intercropping system has been developed as an alternative strategy to improve land-use efficiency, income diversification, and farming sustainability. This study aims to: (1) analyze the influence of land size, farmer age, farming experience, and rainfall on the productivity of the intercropping system; (2) develop sustainable landscape management strategies using SWOT and SWOT matrix analysis; and (3) provide data-driven policy recommendations to support sustainable oil palm plantations. The research methods include multiple linear regression analysis for socio-economic variables, correlation analysis for environmental factors (rainfall), and SWOT analysis to evaluate Strengths, Weaknesses, Opportunities, and Threats  of the intercropping system. The results indicate that land size has a significant positive effect on production, while farming experience shows a significant negative effect. Rainfall has a strong positive correlation with yields, and SWOT analysis positions the intercropping system in a progressive quadrant with promising Opportunities for development. In conclusion, the oil palm–pineapple intercropping system has the potential to enhance productivity, stabilize farmer incomes, and support environmental sustainability. Therefore, diversification-based management strategies and supportive policies are essential to Strengthen the welfare of local communities.